Clinical and Radiological Regeneration of Large and Deep Osteochondral Defects of the Knee by Bone Augmentation Combined With Matrix-Guided Autologous Chondrocyte Transplantation. (November 2017) - Zellner, Johannes; Grechenig, Stephan; Pfeifer, Christian G.; Krutsch, Werner; Koch, Matthias; Welsch, Goetz; Scherl, Madeleine; Seitz, Johannes; Zeman, Florian; Nerlich, Michael; Angele, Peter
Background: Large osteochondral defects of the knee are a challenge for regenerative treatment. While matrix-guided autologous chondrocyte transplantation (MACT) represents a successful treatment for chondral defects, the treatment potential in combination with bone grafting by cancellous bone or bone block augmentation for large and deep osteochondral defects has not been evaluated. Purpose: To evaluate 1- to 3-year clinical outcomes and radiological results on magnetic resonance imaging (MRI) after the treatment of large osteochondral defects of the knee with bone augmentation and MACT. Special emphasis is placed on different methods of bone grafting (cancellous bone grafting or bone block augmentation). Study Design: Case series; Level of evidence, 4. Methods: Fifty-one patients were included. Five patients were lost to follow-up. This left 46 patients (mean age, 28.2 years) with a median follow-up time of 2 years. The 46 patients had 47 deep, large osteochondral defects of the knee joint (1 patient with bilateral defects; mean defect size, 6.7 cm 2 ). The origin of the osteochondral defects was osteochondritis dissecans (n = 34), osteonecrosis (n = 8), or subchondral cysts (n = 5). Depending on the depth, all defects were treated by cancellous bone grafting (defect depth ≤10 mm; n = 16) or bone block augmentation (defect depth >10 mm; n = 31) combined with MACT. Clinical outcomes were followed at 3 months, 6 months, 1 year, 2 years, and 3 years and evaluated using the International Knee Documentation Committee (IKDC) score and Cincinnati score. A magnetic resonance imaging (MRI) evaluation was performed at 1 and 2 years, and the magnetic resonance observation of cartilage repair tissue (MOCART) score with additional specific subchondral bone parameters (bone regeneration, bone signal quality, osteophytes, sclerotic areas, and edema) was analyzed. Results: The clinical outcome scores revealed a significant increase at follow-up (6 months to 3 years) compared with the preclinical results. The median IKDC score increased from 42.6 preoperatively to 75.3 at 1 year, 79.7 at 2 years, and 84.3 at 3 years. The median Cincinnati score significantly increased from 39.8 preoperatively to 72.0 at 1 year, 78.0 at 2 years, and 80.3 at 3 years. The MRI evaluation revealed a MOCART score of 82.6 at 1 year without a deterioration at the later follow-up time point. Especially, the subchondral bone analysis showed successful regeneration. All bone blocks and cancellous bone grafts were integrated in the bony defects, and no chondrocyte transplant failure could be detected throughout the follow-up. Conclusion: Large and deep osteochondral defects of the knee joint can be treated successfully with bone augmentation and MACT. The treatment of shallow bony defects with cancellous bone grafting and deep bony defects with bone block augmentation shows promising results.